Strategic Measures for Food Processing and Manufacturing Facilities to Combat Coronavirus Pandemic (COVID-19) - Muhammad Shahbaz; Muhammad Bilal; Muhammad Akhlaq; Abdul Moiz; Shagufta Zubair; Hafiz M.N. Iqbal (Journal of Pure and Applied Microbiology, 2020)
Coronavirus pandemic (Covid-19) leaves wide-ranging and catastrophic effects at normal ways of living, has disturbed the global food supply chain, and have a damaging impact on food security as well. Food industry and the government should come together to ensure that the food sector should remain open for consistent and unhindered production of food, so consumers have continued access to safe, healthy, and nutritious food during this pandemic. As the countries combat coronavirus pandemic,the food sector must keep gears of food processing and manufacturing moving on to avoid food shortage in the market. To continue the production and supply of safe food at the sites, the food processing and manufacturing facilities have the same level of health challenges which may pose hurdles to consistently of food production. To prevent such issues and critical situation, the food industry needs to take on specific precautions for site and employees to keep them safe and healthy. By appropriately maintaining the food safety systems and with special consideration to combat coronavirus transmission at premises and among employees can help food facilities to not disrupt the flow of manufactured food products and ingredients including food packaging material. Food facilities should strictly monitor staff health, personnel hygiene, and appropriate use of personnel protective equipment at the site entrance and during working and should adopt restrictive visitor policies including suppliers and contractors. Cleaning and disinfection of frequent and high touch points with approved chemicals and sanitizers with defined frequencies and practicing social distances and employee optimization during shifts can be helpful to prevent the spread of coronavirus. The management should limit their visits to the site and monitor the activities by CCTV cameras and food safety audits can be conducted with the use of remote auditing tools. Finally, the facilities should be vigilant to monitor the temperature of staff, employees and visitors, supplier, or contractor to identify if there may any sick person to avoid further spread of coronavirus and shall report to concerned health authorities if anyone symptoms matching with COVID-19.